PENINGKATAN BOBOT PANEN ULAT HONGKONG AKIBAT APLIKASI LIMBAH SAYUR DAN BUAH PADA MEDIA PAKAN BERBEDA - Hartiningsih Hartiningsih; Eka Fita Sari (BUANA SAINS, 2014)
One of potentially husbandry sector and developed are yellow meal worm or hongkong yellow mealworm. This animal could eat many kind of agriculture waste, vegetable, or fruit. The research was done to evaluation the influence of vegetable waste and fruit waste taken from traditional market using different three formulation feed media effect on feed consumption (basicly on dry basis), weight gain, lenght of worm of 50 days, feed cost, and income over feed cost. The research used 6 treatments were P1 (vegetable waste + wheatbran), P2 (vegetable waste + feed media (54% wheatbran+46% cassava waste)), P3 (vegetable waste + feed formulation contains 20% crude protein), P4 (fruit waste + wheatbran), P2 (fruit waste + feed media (54% wheatbran+46% cassava waste)), P3 (fruit waste + feed formulation contains 20% crude protein). All treatments were repeated 4 times. Research method using Completely Randomized Design (CRD). The results showed that treatment using wheatbran + cassava waste giving highest weight gain and IOFC. The using of the mixing wheatbran and cassava waste could increase weight gain and IOFC on all the using vegetable and fruit waste